Household-Based Survey on Knowledge, Attitudes, and Practices towards Dengue Infection and Prevention in a Semi-Urban Area (Ja-Ela MOH Area) - Perera, W.L.S.; Perera, P.K.; Wijesundara, C.; Ambagahawita, A.M.; Fernando, S.U.; Udara, S.; Bandaranayaka, K.O. (International Journal of Medical Parasitology & Epidemiology Sciences, 2021)
Introduction: Dengue is the most prevalent infectious mosquito-borne viral infection in the world. Over time dengue has caused high mortality and morbidity. Methods: A cross-sectional study was conducted to assess the level of knowledge, attitude, and practice among 510 residents of Ja-Ela MOH area using an interviewer-administered questionnaire. Ethical clearance was obtained from the National Institute of Health Science Kalutara. Results: The majority (50.8%) of the respondents were females, and the mean age of the sample was 43.7±16.7 years. The study results showed that 56.5% (n=288), 52.9% (n=270), and 50.7% (n=257) of the sample had good knowledge, attitudes, and practices (KAP) towards dengue prevention, respectively. Good knowledge is significantly associated with 41-60 years of age (odds ratio [OR]=2.513, P<0.001), secondary education or higher (OR=1.857, P=0.008), and a monthly income of LKR 20000–40000 and more than 40000 (OR=0.477, P=0.016; OR=0.440, P=0.015). Non-Sinhalese nationality (OR=0.180, P=0.033) was associated with poor levels of knowledge. Good attitudes towards the prevention of dengue were found in males (OR=2.095, P=0.001), unemployed individuals (OR=1.759, P=0.018), and individuals with a monthly income of<LKR 20000 (OR=2.393, P=0.001). Poor practices towards dengue prevention were found in other nationalities compared to Sinhalese (OR=0.104, P=0.001) while Roman Catholics had poor practices towards dengue prevention (OR=0.677, P=0.041). The study shows that the experience of dengue is positively associated with better attitudes towards dengue prevention (Mann-Whitney U test; P<0.001). Conclusion: KAPs were not significantly correlated with each other. Targeted health education and promotion programmes provided for specific populations should be considered a priority activity
Keywords: Dengue; Knowledge; Attitude; Practices; Sri Lanka